2018
DOI: 10.5465/amj.2016.0416
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Co-location of Partners and Rivals: Implications for the Design of R&D Alliances

Abstract: This study advances previous research on the competitive aspects of R&D collaborations that has been mainly interested in knowledge protection concerns in alliances between direct rivals. We join the alliance and agglomeration literatures and argue that geographic co-location between a focal firm's partner and rivals introduces potential indirect paths of knowledge leakage to rivals.Geographic co-location creates significant risks of unintentional knowledge spillovers to rivals while it also increases the like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 96 publications
(128 reference statements)
0
45
0
Order By: Relevance
“…For instance, a firm may cooperate with multiple alliance partners that compete with each other rather than with the focal firm (e.g., Lavie, ). It may also compete indirectly with another firm by virtue of their independent cooperation with the same alliance partners (Gimeno, ; Ryu, McCann, & Reuer, 2018). Accordingly, scholars should study the distinction between the direct and indirect interplay of competition and cooperation at multiple levels of analysis.…”
Section: A Preliminary Roadmap For Studying the Interplaymentioning
confidence: 99%
“…For instance, a firm may cooperate with multiple alliance partners that compete with each other rather than with the focal firm (e.g., Lavie, ). It may also compete indirectly with another firm by virtue of their independent cooperation with the same alliance partners (Gimeno, ; Ryu, McCann, & Reuer, 2018). Accordingly, scholars should study the distinction between the direct and indirect interplay of competition and cooperation at multiple levels of analysis.…”
Section: A Preliminary Roadmap For Studying the Interplaymentioning
confidence: 99%
“…In fact, Adams (1980) early on suggested that protecting the organization and buffering it from external threats and pressures is one of the critical foci of attention when firms engage in boundary-spanning activities. Ryu, McCann, & Reuer (2018) specifically investigated risks of knowledge losses resulting from 'partner-rival' geographic co-location, and found that effective, alliance governance design choices were important, e.g., by narrowing the scope and reducing the task interdependencies within the alliance. While the extant literature has focused mainly on learning and on the transfer of knowledge and skills, the new IB realities will require a stronger focus on developing mechanisms for buffering key technological capabilities, not only as a function of micro-level frailties, but especially to protect against the vagaries of (neo) techno-nationalist policies.…”
Section: Can Dynamic Capabilities Lead To Renaissance Of the Mne?mentioning
confidence: 99%
“…Examples include cultural distance between parent and foreign subsidiary (D. Shin, Hasse, & Schotter, 2017), vagaries in the IPO process (Kotlar et al, in press; Plummer, Allison, & Connelly, 2016), geographic within-country distance (Ryu, McCann, & Reuer, in press), within-firm diversification (Hitt, Hoskisson, & Ireland, 1994), and decentralization between headquarters and subsidiaries (Ecker et al, 2013). These barriers are often observed in emerging economies (Luo & Chung, 2005; Zhu & Chung, 2014), in political markets where public policy initiatives are “traded” (Bonardi, Hillman, & Keim, 2005), and more broadly in market transactions (Lado & Wilson, 1994; Shane & Venkataraman, 2000; Quinn & Jones, 1995; J.…”
Section: A Review Of Past Accomplishmentsmentioning
confidence: 99%